2022
DOI: 10.3390/app12105229
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Antibacterial Activity of French Mushrooms against Pathogenic and Multidrug Resistant Bacteria

Abstract: In the alarming context of antibiotic resistance, we explored the antibacterial potential of French mushrooms against wild-type and multidrug-resistant (MDR) bacteria. In order to accelerate the discovery of promising compounds, screenings were carried out by TLC-direct bioautography. A total of 70 extracts from 31 mushroom species were evaluated against five wild-type bacteria: Staphylococcus epidermidis, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa. This first sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Extracts were more effective against Gram-positive bacteria in which case microbicidal activity was reported, while in the case of Gram-negative species, extracts were bacteriostatic. The same was observed in this and several other studies [ 34 , 35 , 36 ]. Phenolic compounds and flavonoids have been marked as the molecules responsible for mushrooms’ antimicrobial activity [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Extracts were more effective against Gram-positive bacteria in which case microbicidal activity was reported, while in the case of Gram-negative species, extracts were bacteriostatic. The same was observed in this and several other studies [ 34 , 35 , 36 ]. Phenolic compounds and flavonoids have been marked as the molecules responsible for mushrooms’ antimicrobial activity [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Phenolic compounds and flavonoids have been marked as the molecules responsible for mushrooms’ antimicrobial activity [ 37 ]. It has been reported that Fomitopsis pinicola possesses several compounds that strongly affect multidrug-resistant bacteria [ 36 ]. The same species tested here acted as an inhibitor of bacterial growth, and the alkali extract was more effective (MIC for both tested bacteria was 10 mg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, the efficacy of French mushroom extracts was found to be more pronounced against grampositive bacteria as opposed to their gram-negative counterparts. 20 In a similar fashion, mushroom extracts that were accessible in Malaysia exhibited efficacy against a range of bacteria, such as S. aureus, B. cereus, S. typhimurium, and E. coli, as determined by minimum inhibitory concentrations (MIC values) varying from 500 mg/mL to 1000 mg/ mL. 21 Multidrug-resistant ESKAPE pathogens that were isolated from clinical wound infections exhibited comparable efficacy when treated with methanolic and aqueous extracts of Neoboletus luridiformis and Boletus edulis.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Pure compounds were applied with appropriate volumes with a 100 µL syringe (Hamilton, Bonaduz, Switzerland) onto TLC plates as bands of 2 mm in length, with a CAMAG Linomat 5 (Muttenz, Switzerland) under a stream of nitrogen. Ethyl acetate extracts of clove (Syzygium aromaticum), Fomitopsis pinicola and Hypholoma fasciculare [5] were deposited (50 µg) in the same conditions as bands of 8 mm in length and then eluted with the solvent system methyl tert-butyl ether/tetrahydrofurane/cyclohexane (5:1:4 v/v/v) previously developed [5].…”
Section: Thin-layer Chromatographymentioning
confidence: 99%